(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
يهدف هذا البحث إلى تحليل مساوئ طريقة حساب أطياف توزع كثافة الحالات المستخدمة على نطاق واسع استناداً إلى معطيات التيار الضوئي الثابت، ثم اقتراح طريقة رياضية جديدة تأسيساً على خوارزمية تنظيم تيخانوف لحساب طيف توزع كثافة الحالات المتوضعة في الفجوة الطاقية لأنصاف النواقل غير المتبلورة من النوع a-Si:H (السيلكون غير المتبلور المهدرج) و a-SiC:H (كربيد السيلكون غير المتبلور المهدرج) التي لا تتطلب افتراضات مسبقة حول سلوك الأطياف المحسوبة. ثم عرضنا في هذا البحث الأطياف التجريبية لكثافة الحالات تأسيساً على الطريقة الجديدة المقترحة عند دراسة عينات محضرة بطريقة التذرية في حالة التواترات العالية في جو بلازمي يحتوي غازي الهيدروجين والأرغون. إن تفسير النتائج الحاصلة يرتبط بتغير تركيـز "الأعمـدة" في الأفلام الرقيقـة المدروسة عنـد تغير شروط تكثيف a-Si:H و a-SiC:H. The aim of this search is to analyze disadvantage of the approach used in the distribution spectra calculation of density of states localized in the energy gap [N(E)]. We suggest a new approach of the distribution spectra calculation of N(E) of amorphous semiconductors; amorphous hydrogenated silicon (a-Si:H) and amorphous hydrogenated silicon-carbide (a-SiC:H). In this research, experimental spectra N(E) based on the new suggested approach are presented for the investigated samples, prepared by sputtering in Ar/H plasma atmosphere. Interpretation of the obtained results depends on the change of column concentration, when the condensation conditions of a-Si:H and a-SiC:H are changed.